Development of pedagogical skills of students of technology and pedagogical specialties using STEM technologies - Kovalchuk, Vasyl; Androsenko, Artem; Derevyanchuk, Oleksandr; Volkova, Natalііa; Piven, Yaroslav (Edelweiss Applied Science and Technology, 2024)
The purpose of the research is to theoretically substantiate the issue of incorporating STEM technologies in the educational process of higher education as a means of developing pedagogical skills of students of technology and pedagogical specialities. Additionally, the study aims and to assess the extent of knowledge regarding STEM education among future teachers and their preparedness to effectively integrate STEM projects into their professional practice. We used various methods, including analyzing the existing theoretical works of Ukrainian and foreign authors related to our research topic. We also utilized techniques such as generalization, systematization, and questionnaires. During the experimental research, we focused on determining the levels of awareness regarding STEM education and the preparedness of students of technology and pedagogical specialities to implement STEM projects in their professional roles. Based on the survey results, it was discovered that the majority of future specialists a positive view of utilizing STEM projects as a means to enhance their pedagogical skills.